Determination of Microorganisms in Activated Sludge of Wastewater Treatment Unit (Journal of the College of Basic Education, 2023)
The amount of microorganisms in samples activated sludge frommunicipal wastewater treatment unit at “ Ristomya ” south of Baghdadregion, during different seasons was determined. The total number ofmicroorganisms was greatest during the summer (7.6 x 10 5 cells/ml),whereas the total number of microorganisms was smallest during winter(1.2 x 10 5 cells/ml).The representatives of genus Pseudomonas predominated inquantitative aspect (4.8 x 10 5 cells/ml) , among the bacteria.Actinomycetes were isolated only during the summer months, toreach its total number (1.0 x 10 3 cells/ml ). Molds were found during allseasons, regardless of their small amount in the total number ofmicroorganisms that gave high number (1.0 x 10 3 cells/ml) in winter,whereas yeasts were not found.The application of achieved experiments can help to store theequilibrium in the ratio of the different groups of microorganisms when istrouble in the activated sludge of wastewater treatment unit at extremeregions.